2011
DOI: 10.5897/ajpp11.229
|View full text |Cite
|
Sign up to set email alerts
|

The effects of maximal aerobic exercise on cortisol and thyroid hormones in male field hockey players

Abstract: Some metabolic and endocrine functions might be influenced by exercise and it leads to changed concentrations of hormone secretions in humans. In order to determine the changes of thyroid hormones (THs) related to shuttle run exercise (SRE), 14 field hockey players and their thyroid stimulating hormones (TSH) free T3 (fT3), free T4 (fT4) were included in this study, and cortisol levels were measured three times; before the exercise, just after the exercise and one hour later after exercise. The results of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
(28 reference statements)
1
5
1
Order By: Relevance
“…Contrary to the results of the present study regarding weight gain in the RT + CEE group, Jose [21] concluded that total creatine supplementation with RT did not cause significant changes in body weight and fat free mass after four weeks of RT and creatine consumption. Similarly, Jagim et al [20] found that creatine monohydrate consumption did not significantly reduce body fat percentage in subjects, and despite the increase in weight, the observed changes were not significant.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary to the results of the present study regarding weight gain in the RT + CEE group, Jose [21] concluded that total creatine supplementation with RT did not cause significant changes in body weight and fat free mass after four weeks of RT and creatine consumption. Similarly, Jagim et al [20] found that creatine monohydrate consumption did not significantly reduce body fat percentage in subjects, and despite the increase in weight, the observed changes were not significant.…”
Section: Discussioncontrasting
confidence: 99%
“…Also, in the case of muscle mass, the results showed that leg and arm muscle masses were significantly increased in the RT + CEE group, but no significant changes were observed in the RT + PL group. In similar studies, Jose [21] showed that after four weeks of RT, when creatine supplementation was consumed immediately after exercise, it increased their strength. Gualano et al [16], studying the effect of creatine supplementation and RT, concluded that creatine monohydrate consumption and RT for 24 weeks improved muscle mass and muscle function.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In our study, the aerobic exercise program significantly reduced TSH level among obese women. This is consistent with the findings of Beyleroglu et al (9) and Bansal et al (28) but inconsistent with the findings of Nicoll et al (29). Production and secretion of the thyroid hormones is regulated by TSH, which is secreted from the pituitary gland.…”
Section: Introductionsupporting
confidence: 73%
“…Additionally, many data have provided discordant results concerning associations of circulating TSH and physical activity. In young men both no changes and significant elevation in circulating TSH were noted immediately after maximal aerobic exercise [9][10][11]. In addition it was shown that long term exercise may have different impacts on TSH levels than an acute exercise program [12].…”
Section: Introductionmentioning
confidence: 99%